PEER-TO-PEER LENDING SYSTEM IN HIFDUN MAAL PERSPECTIVE: EVIDENCE FROM THE FINTECH COMPANY OF INVESTREE - Anisa Fadilah Zustika; Ana Toni Roby Candra Yudha (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The technology-based financial management system or so-called financial technology (fintech) has become a trend in the millennial era, both with sharia or conventional labels. This study aims to determine and examine the operational mechanisms and implications of the application of the peer to peer lending system, which is used as a transaction method both in funding and financing. The approach used is qualitative, an approach that prioritizes the subjectivity aspects of researchers and informants. The informants of this study are experts from several stakeholders such as the MUI of East Java, Masyarakat Ekonomi Syariah (MES) branch of Semarang, and 2 sharia fintech business owners and practitioners in East Java. The study results obtained are fintech based on a peer to peer lending system (P2PL) in the perspective of hifdzu mal (Investree company case study) is an online loan transaction that is consistent with the theory of hifdzu maal. The suitability of the transaction with hifdul maal, because each agreement is clear and in accordance with sharia provisions such as fair, mutually committed, and protect ownership. Suggestions from this study are the need for the addition of sharia supervisory board (DPS) for fintech, collaboration with universities in business development so that literacy and inclusion of fintech can be more extensive and developed.Keywords: fintech, peer to peer lending (P2PL), protection of wealth